AI for social good - Philip Treleaven; Daniel Brown (Royal Society Open Science)
This article describes the Generative AI Education (GenAIE) programme: using generative AI (GenAI) to provide personalized education to disadvantaged people, notably probationers and prisoners. For the UK Probation and Prison Service, GenAI (Introducing ChatGPT, 2025, OpenAI; see https://openai.com/blog/chatgpt (accessed January 2025)) is providing education for felons to help stop them reoffending. The UK has over 80 000 prisoners and education is the best deterrent to reoffending, which costs £18bn ($23b) pa (Reoffending Costs, UK Parliament, 2022; see https://questions-statements.parliament.uk/written-questions/detail/2022-0309/137323 (accessed January 2025)). The AI ‘tsunami’ led by GenAI will be hugely disruptive for business and society. However, it also offers pioneering opportunities for social good, notably through personalized education/training for socially excluded and disadvantaged groups (e.g. people on probation, people in prison, refugees, long-term unemployed, long-term sick, low-aspiration young people); thereby transforming their future and addressing major social problems. As a starting point, University College London and MegaNexus are working with educational professionals to produce personalized training content specifically for the Justice sectors, including probation and prisons, described below, which evidences and demonstrates the positive power of GenAI for social benefit. This is part of our AI for Social Good programme. As of 31 November 2024, the GenAIE programme had gained over 53 400 users and accumulated over 596 600 hours of Education, Training and Employment learning. We are now working with local councils to support their social services key workers and their clients. To make our paper self-contained but concise, key technical terms are defined as bullet points.